Japin Ayun Anak Dance: A Collaborative Reflection on Ma'ayun Anak and Ba'ayun Mulud Traditions in South Kalimantan Banjar Community Culture - Putri Yunita Permata Kumala Sari; Rezky Rezky; Muhammad Jazuli; Juju Masunah; Wahyu Lestari (International Conference on Science, Education, and Technology, 2023)
The Banjar people in South Kalimantan have a tradition of putting their children to sleep in a swing while chanting a rhythmic shalawat of Banjar poetry called Ma'ayun Anak. This tradition is integrated into the Ba'ayun Mulud tradition which is a cultural tradition of the Banjar people to ma'ayun a child in the month of Maulid or Rabiul Awwal in the Islamic calendar (Hijriyah) to celebrate the birthday of Rasulullah Muhammad Shalallahu 'Alaihi Wassalam. This cultural reflection collaborated and was expressed in a new dance creation entitled "Japin Ayun Anak" in 2018 by the Posko La Bastari Kandangan, Hulu Sungai Selatan Regency. This article is descriptive qualitative using an ethnochoreological approach to obtain descriptions, meanings and values in the choreography of this dance which includes conceptualized motion, space and time as well as classification of movement types. There are 15 variations of motion in this dance that reflect important messages for appreciators, including regarding the love of parents for their children and the actualization of Muslim gratitude for the birth of Muhammad Shalallahu 'Alaihi Wassalam, in which mothers rock their children accompanied by the Prophet's blessings and prayers for his son. It is hoped that the child who is rocked will inherit the glory of the Prophet Muhammad Shalallahu 'Alaihi Wassalam and obtain safety in this world and in the hereafter.